A Novel Approach to the Design of Axial-Flux Switched-Reluctance Motors - Tim Lambert (Machines, 2015)
This paper presents the design of a new axial-flux switched-reluctance motor (AFSRM) topology for in-wheel drive vehicle applications. The features of the topology include a short flux path and an outer-rotor configuration. The proposed topology also uses a sintered-lamellar soft magnetic composite core material, and permits displacement of the rotor along the suspension axis, which reduces damage to the stator caused by impacts and vibrations. The combination of these features makes this new topology competitive with other in-wheel motors in regard to torque density, durability, and cost. To describe the behaviour of the topology, a model of the topology is developed using a new integral inductance function. That model is used to select the design parameters of an 8/6 AFSRM, for which a fuzzy controller is also developed to control the phase current. Several simulations of the 8/6 AFSRM are performed to calculate its energy conversion efficiency, thermal performance, and torque density, and results indicate that the new AFSRM has a higher energy conversion efficiency, and can produce more torque/kg than other switched-reluctance motors used for in-wheel drive vehicle applications.